Respuesta :

Answer:

f(a + 2)= (5 + a) / (a - 1) or f(a+2)= (a+5)/(a-1)

Step-by-step explanation:

f(x)=(3+x)/(x-3)

To evaluate f(a+2), simply replace the x with a+2

f(a+2) = (3 + a+2)/(a+2 - 3)= (a+5)/(a-1)

or

To answer items such as this, we directly substitute the a + 2 to the all the x's in the function:

f(a + 2) = (3 + a + 2) / (a + 2 - 3)

Simplifying the function generated above:

f(a + 2) = (5 + a) / (a - 1)

Step-by-step explanation:

f(x) = 3+x/x-3

Substituting x = a+2, we get

[tex]f(a + 2) = \frac{3 + (a + 2)}{(a + 2) - 3} \\ f(a + 2) = \frac{a + 5}{a - 1} [/tex]

which is the final answer.

Please mark Brainliest if this helps!